Infrastructure as Code (IAC) Cookbook - Jourdan, Stephane; Jourdan, Stephane; Pomes, Pierre (Packt Publishing, 2017)
Over 90 practical, actionable recipes to automate, test, and manage your infrastructure quickly and effectivelyAbout This BookBring down your delivery timeline from days to hours by treating your server configurations and VMs as code, just like you would with software code.Take your existing knowledge and skill set with your existing tools (Puppet, Chef, or Docker) to the next level and solve IT infrastructure challenges.Use practical recipes to use code to provision and deploy servers and applications and have greater control of your infrastructure.Who This Book Is ForThis book is for DevOps engineers and developers working in cross-functional teams or operations and would now switch to IAC to manage complex infrastructures.What You Will LearnProvision local and remote development environments with VagrantAutomate production infrastructures with Terraform, Ansible and Cloud-init on AWS, OpenStack, Google Cloud, Digital Ocean, and moreManage and test automated systems using Chef and PuppetBuild, ship, and debug optimized Docker containersExplore the best practices to automate and test everything from cloud infrastructures to operating system configurationIn DetailInfrastructure as Code (IAC) is a key aspect of the DevOps movement, and this book will show you how to transform the way you work with your infrastructure$1 (Bby treating it as software.This book is dedicated to helping you discover the essentials of infrastructure automation and its related practices; the over 90 organized practical solutions will demonstrate how to work with some of the very best tools and cloud solutions.You will learn how to deploy repeatable infrastructures and services on AWS, OpenStack, Google Cloud, and Digital Ocean. You will see both Ansible and Terraform in action, manipulate the best bits from cloud-init to easily bootstrap instances, and simulate consistent environments locally or remotely using Vagrant. You will discover how to automate and test a range of system tasks using Chef or Puppet. You will also build, test, and debug various Docker containers having developers' interests in mind.This book will help you to use the right tools, techniques, and approaches to deliver working solutions for today's modern infrastructure challenges.Style and approachThis is a recipe-based book that allows you to venture into some of the most cutting-edge practices and techniques about IAC and solve immediate problems when trying to implement them.s